Shiv’im Shanah dan Koach Gvurot : Studi Hermeneutik tentang Kefanaan Manusia dalam Mazmur 90:10 - Wennar Wennar; Yohanes Rahdianto Suprandono (Majalah Ilmiah METHODA, 2024)
This study examines Psalm 90:10 through a hermeneutic approach to understand the phrases "Shiv'im Shanah" (seventy years) and "Koach Gvurot" (eighty years of strength) in the context of Hebrew theology and literature. This study highlights the traditional interpretation that often interprets this verse as a limit on human lifespan, and explores its historical, literary, and theological context. Using qualitative research methods based on literature study and a Gadamerian hermeneutic approach, this article offers a new perspective that considers the original author's intent, contextual relevance, and theological implications for the contemporary church. This study shows that this verse does not simply set a limit on human lifespan, but highlights the existential limitations of humans before the eternal God. These findings provide new insights into how this verse can be applied in the theological teaching of the contemporary church, especially in reflections on wisdom, mortality, and dependence on God.